Non-Gaussian turbulence induced buffeting responses of long-span bridges based on state augmentation method. (1st March 2022) - Cui, Wei; Zhao, Lin; Ge, Yaojun
Abstract: Traditionally, the structural turbulence-induced buffeting vibrations is analyzed along the famous Davenport chain through turbulence, wind loads and structural response based on one fundamental assumption: the random processes about the above three subsequent stages should be all Gaussian process. This assumption simplifies the mathematical derivation of turbulence-induced vibration, and were widely used in field of wind engineering for structures. However, several recent studies reveal that turbulence with non-Gaussian distribution is observed in the boundary-layer atmosphere during wind storm events, especially typhoons or hurricanes. For the turbulence-induced vibration, traditional Gaussian assumption may lead to non-conservative results, especially for non-Gaussian turbulence with positive skewness. Based on the state augmentation method, this paper derives formulations to calculate the moments of buffeting response. The non-Gaussian turbulence-induced buffeting forces are approximated by Hermite polynomials of the underlying Gaussian process, modeled as Ornstein–Uhlenbeck process in the state augmentation method. The state augmentation method is verified for bridge buffeting vibration caused by Gaussian turbulence, and the approximation of buffeting force by the Ornstein–Uhlenbeck process is also validated. Applying the state augmentation method on the bridge buffeting response excited by non-Gaussian turbulence, the corresponding bridge buffeting response RMS, skewness and kurtosis can be computed sequentially. The results show that the RMS of buffeting responses induced by non-Gaussian turbulence is slightly higher than Gaussian turbulence results. However, the extreme responses are greatly affected by the skewness of non-Gaussian turbulence. Highlights: State augmentation formulas are derived for buffeting induced by non-Gaussian turbulence. Bridge buffeting excited by Gaussian turbulence from proposed method are verified. High-order moments of turbulence can be transferred to responses because of damping. Buffeting extreme responses affected by non-Gaussian turbulence are increased.